Does environmental data disclosure drive environmental performance? a case study of water consumption in gold mining in South Africa - Moodley, Nevashree (My University, 2020)
There are various sustainability reporting guidelines that companies can comply with to disclose information to understand their environmental performance. Some guidelines like the Global Reporting Initiative (GRI) may be a requirement for listed companies while other guidelines may be voluntary. While these guidelines are noted for reporting purposes, the inherent benefit will be to therefore manage and reduce impacts as they are being measured. Therefore, this research was to verify whether the disclosure of annual environmental information led to improved environmental performance over a 5-year period. The specific data that were analysed were consumption and recycling of water from two gold mining companies in South Africa. Through the perusal of published data, the data were tabled, graphed and trends analysed. It was deduced that there was a relationship between environmental disclosure and environmental performance as the performance of the company could be evaluated based on the disclosure of environmental data. There had also been an improvement in the quality of data and more importantly in the environmental performance in the companies selected which was driven by the disclosure requirements for each reporting guideline. The improvement in the readability of the reports over the 5-year research period was also noted and the information disclosed was extensive in the aim to meet the various guideline requirements. From the interview process, it was clear that reporting to different guidelines is a lengthy process and for that the International Council on Mining and Metals water guideline was the most preferred option for both mining companies. The information was tedious to collect but the understanding and willingness to be as transparent as possible was noted. Both companies listed data to highlight the variances but noted that improvement was driven from their respective operational mining sites. While the relationship was demonstrated to be positive between the environmental disclosure and environmental performance, significant improvement in the water data published was not found. There would need to be a stronger focus on objectives and targets as required by the CDP water questionnaire and the ISO 14001 management system to drive environmental improvement that has an impact on the natural surroundings
A research report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science, 2020
Keywords: Environmental auditing; Corporation reports--Environmental aspects--South Africa